Analisa Keimanan Mahasiswa dalam Pembelajaran Pendidikan Agama Islam secara Daring: Perspektif Psikologi - Wira Yudha Nuswantoro; Handre Syahrul Fanani; Erwin Kusumastuti (IAIN Bone, 2021)
Islamic Religious Education is an important thing that needs to be taught to every student. By studying Islam, students should be able to become individuals who have noble morals, have a stand, and can be an example for others. In the current pandemic situation, it requires all learning to be carried out online, including learning Islamic Religious Education. This raises concerns for educators whether online learning can increase student faith. With these problems, research is needed to analyze the level of faith in online Islamic Religious Education from a psychological perspective. The study used qualitative data collection methods through questionnaires and in-depth interviews with 70 correspondents who were Industrial Engineering Students of UPN